Chemical integration of reduced graphene oxide sheets encapsulated ZnCo2O4 quantum dots achieving excellent capacity storage for lithium-ion batteries. (10th August 2017) - Chen, Chang; Lam, Kwok-ho; Liu, Bao-jun; Hou, Xian-hua; Wu, Yu-ping
Abstract: Chemically integrated hybrid quantum dots ZnCo2 O4 /reduced graphene oxide (QDs ZCO/rGO) sheets nanocomposites are synthesized through polyol processes. rGO sheets grow and interweave to form basic skeletons. Ultrafine ZCO particles with a size of around 3.66 nm grow and embed on both sides of the rGO sheets, and the rGO sheets restrain the reunion of ZCO nanoparticles. The existence of rGO sheets and ZCO nanoparticles can engender the mutual synergistic effects so that hybrid QDs ZCO/rGO electrodes exhibit the excellent electrochemical properties. Owing to this special nanoparticles-on-sheets structure, the hybrid QDs ZCO/rGO electrodes exhibit an excellent initial discharge capacity for rechargeable lithium-ion batteries (1325.9 mAh g −1 at the current density of 200 mA g −1 ), high rate stability (532.3/566.1 mAh g −1 at 4000 mA g −1 ) and outstanding electrochemical cyclic stability (657.6/668.2 mAh g −1 at 2000 mA g −1 after 2000 cycles with a capacity retention of 68.6%). For full-cells, high initial reversible discharging capacity (646 mAh g −1 at 200 mA g −1 ) and good cyclic stability (514 mAh g −1 at 200 mA g −1 after 100 cycles) are obtained. The superior performance of the as-prepared electrodes is ascribed to the advantage of nano-sized particles. With the successful synthesis of hybrid QDs ZCO/rGO nanocomposites, the facile synthetic route and unique growth of nanostructuring method can be extended to high electrochemical performance electrodes for commercial lithium-ion batteries.